Surgical options for treatment of lip and perioral tumors: report of 5 cases - Priscilla Spina; Alessandra Drummond; Fernanda Campany; Anna Beatriz Celano Novellino; Joaquim Mesquita Filho (Sociedade Brasileira de Dermatologia, 2014)
Basal cell and squamous cell carcinomas are the main neoplasms of lip and perioral location. We describe different techniques of successful surgical reconstruction, including flaps or simple incision and suture. Using the latter technique satisfactory results were demonstrated, although the incision made removed more than a third of the lip, contrary to the literature. Our goal is to emphasize that the common sense and experience of the surgeon should prevail in the choice of reconstructive method. Moreover, even if the priority is complete excision of the lesion, we cannot ignore the aesthetic and functional recovery objective.